2008
DOI: 10.1091/mbc.e08-05-0483
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Intermediate Chain: An Essential Subunit That Contributes to Spindle Checkpoint Inactivation

Abstract: The dynein light intermediate chain (LIC) is a subunit unique to the cytoplasmic form of dynein, but how it contributes to dynein function is not fully understood. Previous work has established that the LIC homodimer binds directly to the dynein heavy chain and may mediate the attachment of dynein to centrosomes and other cargoes. Here, we report our characterization of the LIC in Drosophila. Unlike vertebrates, in which two Lic genes encode multiple subunit isoforms, the Drosophila LIC is encoded by a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 87 publications
(142 reference statements)
7
75
0
Order By: Relevance
“…We have now found that the deletion of Dlic1 in mouse leads to the destabilization of DHC, DIC and DLC (Tctex-1) in many mouse tissues or cells, such as retinas and MEFs, but does not affect DLIC2. Our findings support the notion that the assembly of core dynein subunits, including the DHC, DIC and DLIC, is an interdependent process [10]. The discrepancy about the effect of DLIC1 on the stability of the dynein complex or subcomplex between HeLa cells and our Dlic1-deficient mouse cells may result from the different methods used to deplete DLIC1: knockdown by RNAi may not completely eliminate DLIC1 but our Dlic1 −/− mouse is a null mutant.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…We have now found that the deletion of Dlic1 in mouse leads to the destabilization of DHC, DIC and DLC (Tctex-1) in many mouse tissues or cells, such as retinas and MEFs, but does not affect DLIC2. Our findings support the notion that the assembly of core dynein subunits, including the DHC, DIC and DLIC, is an interdependent process [10]. The discrepancy about the effect of DLIC1 on the stability of the dynein complex or subcomplex between HeLa cells and our Dlic1-deficient mouse cells may result from the different methods used to deplete DLIC1: knockdown by RNAi may not completely eliminate DLIC1 but our Dlic1 −/− mouse is a null mutant.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, Dlic1 deficiency-mediated imbalance of cargo transportation between plus-and minus-end directions in cells The role of DLIC proteins in the assembly of the core dynein complex has been controversial. The DLIC protein is required for the stability of both the DHC and DIC in Drosophila and Aspergillus, and is able to stabilize the interaction between DHC and DIC in Aspergillus [10,15]. However, depleting DLIC1 or DLIC2 [11,14] by RNAi in HeLa cells did not affect the protein levels of DHC, DIC and DLC (Tctex-1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations